The Problem of Integration of Lithuania Minor and Lithuania Major - Pocytė, Silva (Sociologija. Mintis ir veiksmas, 2001)
The aim of the article is to analyze the relation between Lithuania Major and Lithuania Minor at the end of the XIX and in the beginning of the XX century. The author argues that the question of integration was problematic despite the common language and the interaction between the regions in the time of the Lithuanian press ban. The author suggests that the reasons of the divide are connected with the differences of religious traditions and develops the argument by analyzing the societal self-understanding of Lithunians in Lithuania Minor.